Proyecto colonial y control ideológico. El establecimiento de la Inquisición en el Perú - Guibovich Pérez, Pedro (1994)
In this article the author analyses the reasons why the Spanish state established the Tribunal de la Inquisición in the Viceroyalty of Peru in 1569. lt claims that this institution was part of a colonial political design thought up by Felipe II at the end of 1560, and that its purpose was to deal with the political and ideological crisis generated by the colonial scheme itself.